1997
DOI: 10.2307/2446149
|View full text |Cite
|
Sign up to set email alerts
|

Concepts and terminology of apical dominance

Abstract: Apical dominance is the control exerted by the shoot apex over lateral bud outgrowth. The concepts and terminology associated with apical dominance as used by various plant scientists sometimes differ, which may lead to significant misconceptions. Apical dominance and its release may be divided into four developmental stages: (I) lateral bud formation, (II) imposition of inhibition on lateral bud growth, (III) release of apical dominance following decapitation, and (IV) branch shoot development. Particular emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
189
0
9

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(209 citation statements)
references
References 34 publications
5
189
0
9
Order By: Relevance
“…Brown 1974;Shimizu-Sato and Mori 2001). It is envisaged that in a tree, active apical meristem releases auxin that inhibits the growth of lateral buds (apical dominance) so when the apex is removed (by flowering or pruning), the apical dominance stops and lateral buds awake (Brown 1974;Cline 1997)…”
Section: Modularity and The Tree Architecture Of The Dragon Treementioning
confidence: 99%
See 1 more Smart Citation
“…Brown 1974;Shimizu-Sato and Mori 2001). It is envisaged that in a tree, active apical meristem releases auxin that inhibits the growth of lateral buds (apical dominance) so when the apex is removed (by flowering or pruning), the apical dominance stops and lateral buds awake (Brown 1974;Cline 1997)…”
Section: Modularity and The Tree Architecture Of The Dragon Treementioning
confidence: 99%
“…Reiteration may also occur by means of growing massive aerial roots. They grow in response to trauma and environmental stress turning large, multi-modular units with a few sets of branches into new clones (Krawczyszyn and Krawczyszyn 2014), that is hard to explain in terms of apical dominance and auxin release, factors that play a role in reiteration of forest trees (Brown 1974;Cline 1997).…”
Section: Reiteration Also Involves Other Growth Hormones and Genetimentioning
confidence: 99%
“…Apical dominance is defined broadly as "the inhibitory control of the shoot apex over the outgrowth of lateral buds" (Cline, 1997;Napoli et al, 1999). Apical dominance acts as a plant survival mechanism by providing a reservoir of meristems that can replace the damaged primary shoot.…”
Section: Biological Functions Of Dormancy and Apical Dominancementioning
confidence: 99%
“…Interestingly, phosphate starvation in plants leads to a reduced number of shoot branches (Troughton 1977;Cline, 1997) and changes in the root system (Ló pez- Bucio et al, 2002;Al-Ghazi et al, 2003;Ma et al, 2003;Nacry et al, 2005;Sánchez-Calderó n et al, 2005). In Arabidopsis, it has been demonstrated that upon phosphate starvation, auxin activity in the root system is altered, leading to a drastic modification of the root morphology (Williamson et al, 2001;López-Bucio et al, 2002;Ma et al, 2003;Nacry et al, 2005;Sánchez-Calderó n et al, 2005).…”
mentioning
confidence: 99%